2002
DOI: 10.2134/jeq2002.1071
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous Oxide Emissions from an Ultisol of the Humid Tropics under Maize–Groundnut Rotation

Abstract: Nitrous oxide (N20) contributes to global climate change and agricultural soils seem to be the major source. Lack of information led to this study on the influence of different amounts and sources of nitrogen on N2O emission from a maize (Zea mays L.)-groundnut (Arachis hypogae L.) crop rotation in an Ultisol of the humid tropics. The treatments were: inorganic N + crop residues (NC), inorganic N only (RN), and half of inorganic N + crop residues + chicken manure (NCM). The corresponding amount of N applied wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
1
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 32 publications
3
34
1
2
Order By: Relevance
“…A negative value indicates low N 2 O emission, where gradient of slope is less. These views are supported by other researchers as well 16,17 . Table 1).…”
Section: Resultssupporting
confidence: 73%
“…A negative value indicates low N 2 O emission, where gradient of slope is less. These views are supported by other researchers as well 16,17 . Table 1).…”
Section: Resultssupporting
confidence: 73%
“…3.2.1) especially nitrous oxide reductase is reported to be sensitive to soil O 2 level, while anaerobic soils and sediments will generate both N 2 O and N 2 . A number of studies have reported higher amounts of N 2 than N 2 O at lower O 2 partial pressure and WFPS above 70% (Eriksen & Hartwig, 1993;Dendooven et al, 1999;Kwong et al 1999, Khalil et al, 2002. Aulakh et al (2001) reported that gaseous N losses as N 2 O after application of urea (120 kg ha -1 ) to flooded rice were 8 to 10 times higher than those of upland wheat because of the anaerobic conditions in the former.…”
Section: Soil Aeration and Water Statusmentioning
confidence: 99%
“…These areas include; urine patches in grazed pastures, where up to 1,000 kg N ha -1 can be found Zaman & Blennerhassett., 2010), riparian wetlands (Nguyen et al, 1999;Matheson et al, 2003), drains and ditches, and stream or river channels (Garcia-Ruiz et al, 1998;Bronson & Fillery, 1998;Mcmahon & Dennehy, 1999;Walker et al, 2002;Zaman et al, 2008b&c, Zaman & Nguyen, 2010. However denitrification can also occur in less obviously waterlogged areas within the agricultural landscape due to the existence of anaerobic microsites such as in the center of soil aggregates (Parkin, 1987) or in areas of localized high O 2 consumption (hot spots), which are created by decaying organic C (Burton et al, 1999;Godde & Conrad, 2000;Khalil et al, 2002;Mosier et al, 2002). Depending on soil physical and chemical conditions, other processes like chemo-denitrification can result in substantial production of N 2 O.…”
Section: Denitrificationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, annual rainfall in their study was much lower (~700 mm) compared to the study presented here (1292 mm). Khalil et al (2002) reported cumulative N2O emissions of 0.83% per total N applied (400 kg N ha -1 ) from chicken manure application in Malaysia (annual rainfall: 2293 mm), but the manure was applied in combination with inorganic N in this study.…”
Section: Cumulative Greenhouse Gas Emissionsmentioning
confidence: 78%